2014
DOI: 10.1177/1065912914563548
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Health into Studies of Political Behavior

Abstract: We argue that research on political behavior, including political participation, public opinion, policy responsiveness, and political inequality will be strengthened by studying the role of health. We then provide evidence that health matters for voter turnout and partisanship. Using the General Social Survey (GSS) and The National Longitudinal Study of Adolescent Health (Add Health), we find that people who report poor health are less likely to vote and identify with the Republican Party. Moreover, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 85 publications
4
112
2
Order By: Relevance
“…Nonetheless, this new work provides important groundwork to validate the potential importance of health to help explain variation in political participation. Self-reported overall health is associated with higher self-reported voting in cross-national studies (Goerres 2007; Mattila et al 2013; Söderlund and Rapeli 2015) and in the U.S. at the aggregate (Blakely, Kennedy, and Kawachi 2001) and individual levels (Pacheco and Fletcher 2015). One study found that more days in the hospital correlated with decreased turnout in Danish elections (Bhatti and Hansen 2012), while those with physical disabilities register and vote less (Clarke et al, 2011; Schur, Kruse, and Blanck 2013).…”
Section: Health and Political Participationmentioning
confidence: 99%
“…Nonetheless, this new work provides important groundwork to validate the potential importance of health to help explain variation in political participation. Self-reported overall health is associated with higher self-reported voting in cross-national studies (Goerres 2007; Mattila et al 2013; Söderlund and Rapeli 2015) and in the U.S. at the aggregate (Blakely, Kennedy, and Kawachi 2001) and individual levels (Pacheco and Fletcher 2015). One study found that more days in the hospital correlated with decreased turnout in Danish elections (Bhatti and Hansen 2012), while those with physical disabilities register and vote less (Clarke et al, 2011; Schur, Kruse, and Blanck 2013).…”
Section: Health and Political Participationmentioning
confidence: 99%
“…Good self-assessed health (Denny & Doyle 2007a, 2007bMattila et al 2013;Pacheco & Fletcher 2015) has also been shown to be independently associated with electoral participation. Poor health can hamper voting propensity via various mechanisms.…”
Section: Path 3: Class-health-turnoutmentioning
confidence: 99%
“…In the resource model (Brady et al 1995), which is the most commonly used framework in studying turnout at the individual level (Smets & Van Ham 2013), unequal levels of participation between socioeconomic groups can be attributed to unevenly distributed participation-fostering resources. Here, we test the effect of two such resources -income and health -which have been chosen because both of them differ substantially between social classes across all countries where reliable data are available (for income, see, e.g., Goldthorpe & McKnight 2006;Weeden et al 2007;Bihagen 2008; for health, see, e.g., Phelan et al 2004;Mackenbach et al 2008;Kunst & Roskam 2010;Toch-Marquardt et al 2014) and are known to predict higher voter turnout, at least in the democratic high-income countries (for income, see, e.g., Leighley & Nagler 2013;Kasara & Suryanarayan 2015; for health, see, e.g., Mattila et al 2013;Pacheco & Fletcher 2015;Sund et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Public health concerns can generally limit individuals’ willingness and ability to vote: any health issue can distract from electoral engagement (Reitan ; Pacheco & Fletcher ). Indeed, previous studies have seen turnout‐dampening effects of specific conditions including depression (Ojeda ) and disability (Schur & Kruse ; Miller & Powell ).…”
Section: Illness and Votingmentioning
confidence: 99%
“…Such forces undoubtedly matter, but ostensibly non‐political characteristics may, too. Personal health, in particular, has recently been shown to matter for voting (e.g., Denny & Doyle ; Mattila et al ; Matsubayashi & Ueda ; Gollust & Rahn ; Pacheco & Fletcher ). Yet communicable diseases, which can sweep through communities and abruptly immobilize large swathes of the population, have received little attention.…”
Section: Introductionmentioning
confidence: 99%